2013
DOI: 10.1007/s00436-013-3299-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic diversity of Entamoeba species infecting macaques in southwest China

Abstract: Many colonies of macaques (Macaca fascicularis and Macaca mulatta) are maintained in China, especially in Guangxi and Guizhou. A total of 803 fresh stool samples infected with Entamoeba were obtained from three big colonies of macaques located in southwest China. The samples were examined for the presence of five Entamoeba species using PCR. Entamoeba nuttalli, Entamoeba dispar, Entamoeba coli, and Entamoeba chattoni infections were detected, but Entamoeba histolytica infection was not. This study is the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
1
15
2
Order By: Relevance
“…We recently reported a high prevalence of E. nuttalli , E. chattoni and E. coli infections in wild macaques, such as rhesus macaques, long‐tailed macaques and Japanese macaques (Feng et al. , ; Tachibana et al. , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported a high prevalence of E. nuttalli , E. chattoni and E. coli infections in wild macaques, such as rhesus macaques, long‐tailed macaques and Japanese macaques (Feng et al. , ; Tachibana et al. , ).…”
Section: Discussionmentioning
confidence: 99%
“…We have isolated E. nuttalli strains from rhesus macaque ( Macaca mulatta ), long‐tailed macaque ( Macaca fascicularis ) and Japanese macaque ( Macaca fuscata fuscata ) (Feng et al. ; Suzuki et al. ; Tachibana et al.…”
mentioning
confidence: 99%
“…To date, we have isolated E. nuttalli from M. mulatta (Feng et al. ; Tachibana et al. , ), Macaca fascicularis (Takano et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that E. nuttalli is prevalent even in wild rhesus macaques in China and Nepal (Feng et al. ; Tachibana et al. ).…”
mentioning
confidence: 99%
“…dispar , since they have been identified using only microscopy (Nurcahyo et al, 2017). The majority of studies of Entamoeba species infecting NHPs using molecular techniques have failed to detect E. histolytica , though often they found E. dispar (Feng et al, 2011, 2013; Jirků‐Pomajbíková et al, 2016; Rivera & Kanbara, 1999; Tachibana, Cheng, Kobayashi, Fujita, & Udono, 2000; Tachibana et al, 2001); recently E. histolytica has been identified in baboons, chimpanzees, and gorillas (Deere et al, 2018; Vlčková et al, 2018). Also, Entamoeba nuttalli , was discovered, which is closely related to E. histolytica (Tachibana et al, 2007).…”
Section: Introductionmentioning
confidence: 99%